Changes in luteinizing hormone secretion after estradiol treatment in prepubertal Nelore heifers - Cardoso, Daniel (2011)
Changes in luteinizing hormone (LH) secretion after 17β-estradiol (E 2) injection were evaluated during sexual maturation in 10 prepubertal Nelore heifers. Heifers were divided into 2 groups: intact (I) and ovariectomized (OVX). 17β-estradiol (2 μg/kg) was administered to both groups at 10, 13, and 17 mo of age. Only at 10 mo of age was there a greater mean LH concentration in OVX heifers (1.33 ± 0.29 ng/mL) compared with the I group (0.57 ± 0.15 ng/mL). At 13 and 17 mo of age there was no significant difference between the 2 groups in any of the evaluated variables (number of peaks, total peak area, greatest peak area, and time to greatest peak occurrence). This suggests a decrease in negative E 2 feedback associated with an increase in positive feedback to LH secretion during sexual maturation, and these were likely the key factors that determined the time of first ovulation in Nelore heifers.